Iodination of acetamides using iodine and iodic acid under conventional method as well as microwave irradiation technique - Patil, Arvind; Zangade, Sainath; Vibhute, Archana; Kalyankar, Sarla (International Multidisciplinary Research Journal, 2012)
Iodoacetamides were synthesized by iodination using iodine and iodic acid as an iodinating reagent in ethanol under conventional method as well as microwave irradiation. Microwave technique has several advantages over conventional technique in terms of simple reaction procedure, easy work up and yields of product.